DEVELOPING DESCRIPTIVE READING MATERIALS ABOUT PALEMBANG HISTORICAL BUILDINGS - Arko Nica; Ismail Petrus; Machdalena Vianty (University of Kuningan, 2021)
The purpose of this study was to find out the validity, practicality, and potential effect of developed descriptive reading materials about historical buildings. The developed reading materials were for the seventh-grade students. The development research was based on Akker’s three phases: 1) analysis, 2) design, and 3) evaluation and revision. In the evaluation phase, the formative evaluation modified by Tessmer was applied and there were five stages: self-evaluation, expert review, one-to-one evaluation, small group evaluation, and field test evaluation. The validity was determined based on the results of the experts’ review and the product was valid which was categorized as high validity. The practicality was determined based on the result of the one-to-one evaluation and the small group evaluation. The product was categorized as very high practical level. The potential effect was evaluated in the field test. The result showed that the product has a potential effect since the students reached the passing grade score. In conclusion, the developed descriptive reading materials about Palembang historical buildings were valid, practical, and has potentially effective for the seventh-grade students.